Taxation, Unemployment and Growth: Dynamic Welfare Effects of "Green" Policies - Brita Bye (Statistics Norway, Research Department, 1996)
This paper analyses the effects of so-called "green" tax reforms on a small, open economy producing an imperfect substitute for foreign goods, using an intertemporal general equilibrium model. The labour market is characterised by union wage setting, and a fixed exchange rate implies wage rigidity and involuntary unemployment. The long run effects on instantaneous utility, employment and the stock of real and financial capital of a revenue neutral increase in the tax on fossil fuels combined with a) lump sum rebating or b) change in the labour income tax rate, are discussed. Due to the changes in instantaneous utility during the time path following the implementation of the tax reform, the total welfare effect may be positive even with a reduction in long run consumption. The total welfare effect is in general more positive (or less negative) with wage tax reduction than lump-sum rebating.
Keywords: D50; D60; D90; H20; J51; Q43; 330; Dynamic equilibrium analysis; Unemployment; Environmental tax reforms.